DNA vaccination of poultry: The current status in 2015. Issue 2 (4th January 2016) - Meunier, Marine; Chemaly, Marianne; Dory, Daniel
Highlights: Poultry DNA vaccination studies are regularly being published since 1993. These studies are mainly, but not only, concerned with vaccination against viruses. The different strategies of improving DNA vaccine efficacies are presented. The fate of the vaccine plasmid, immune properties and other applications are described. Despite the compiling preclinical reports, a poultry DNA vaccine is yet unavailable in the market. Abstract: DNA vaccination is a promising alternative strategy for developing new human and animal vaccines. The massive efforts made these past 25 years to increase the immunizing potential of this kind of vaccine are still ongoing. A relatively small number of studies concerning poultry have been published. Even though there is a need for new poultry vaccines, five parameters must nevertheless be taken into account for their development: the vaccine has to be very effective, safe, inexpensive, suitable for mass vaccination and able to induce immune responses in the presence of maternal antibodies (when appropriate). DNA vaccination should meet these requirements. This review describes studies in this field performed exclusively on birds (chickens, ducks and turkeys). No evaluations of avian DNA vaccine efficacy performed on mice as preliminary tests have been taken into consideration. The review first describes the state of the art for DNA vaccination in poultry: pathogens targeted, plasmids used and different routes of vaccine administration. Second, it presents strategies designed to improve DNA vaccine efficacy: influence of the route of administration, plasmid dose and age of birds on their first inoculation; increasing plasmid uptake by host cells; addition of immunomodulators; optimization of plasmid backbones and codon usage; association of vaccine antigens and finally, heterologous prime-boost regimens. The final part will indicate additional properties of DNA vaccines in poultry: fate of the plasmids upon inoculation, immunological considerations and the use of DNA vaccines for purposes other than preventing infectious diseases.